Development of test operations of different duration in terms of input for the verification of efficiency formula - Lutsenko, Igor; Fomovskaya, Olena; Serdiuk, Olga; Baranovskaya, Mila; Fomovskyi, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2018)
Determining an indicator for the estimation of effectiveness of system operations is an important stage for optimization of technological processes of any enterprise. This step predetermines the established mode of functioning of all its system processes. The fact that all technological processes should be optimized using an agreed optimization criterion is an axiom. Such a possibility appears only in one case – if we apply the efficiency formula as an optimization criterion in all functional systems. This approach maximizes financial possibilities of the owner of an enterprise. The problem is to identify a structure that corresponds to the structure of the original efficiency formula among a set of evaluation indicators that are identical in terms of formal characteristics. There are classes of standard models of operations define now for the practical solution of this problem. Each of them has its own functional orientation. The most developed are the classes of reference models of simple operations. In relation to the classes of reference models of operations with distributed parameters, there is a solution of the problem operational processes with the same duration in time, as well as for processes with different duration of resource expense by an output. In the proposed study, we define a limited class of models of operations with distributed parameters of different duration by an input. The creation of such a class of operations is quite a difficult task, since it is necessary to take into account a time factor and to enable possibility of comparison of operational processes of different duration. To solve this problem, at the first stage, we formed global models of simple operations of different duration with predetermined rating efficiency. At the next stage, we formed reference models of operations with distributed parameters by an output of different duration by compositing. The development of the verification method by determining a class of operations with distributed parameters in terms of input of different duration in time improves reliability of verification results of the estimated indicator significantly. It is necessary to perform the verification procedure whenever we intended to use it as an indicator of effectiveness